KEMAMPUAN LITERASI SAINS SISWA PADA MATERI EKOSISTEM DI SMA NEGERI 3 TARAKAN KALIMANTAN UTARA - Syarifah Novianur Muhammad; Listiani Listiani; Aidil Adhani (Universitas Lambung Mangkurat, 2018)
Abstract. Research on scientific literacy aimed to analysis XI IPA students’ scientific literacy on ecosystem topic. This research carried out at SMA Negeri 3 Tarakan, Kalimantan Utara, from August – September 2017. This research was used descriptive qualitative method. Sampling technique was used simple random sampling technique. There were 34 of students at XI IPA class that have learned ecosystem topic and they were the research sample. The instrument used to measure of students’ scientific literacy was an essay questions and it consisted of 15 questions related to scientific literacy. Data was analyzed through an assessment interpretation formula. Overall, the result showed that 53% respondents has the scientific literacy in “enough category”.Keywords: scientific literacy, ecosystem, students’ scientific literacy ability